NILAI-NILAI PENDIDIKAN ISLAM DALAM AL-QUR’AN SURAT ALI IMRAN AYAT 37 - Chumaidah Syc; Yuni Astutik (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2020)
Abstract: Islamic education is an important part in the world of education. Because humans not only need knowledge, but also need spiritual power of religion to form a whole human being (insan kamil) in accordance with Islamic norms. This study discusses "Islamic Education Values ??Contained in the Qur'an, Surat Ali Imran Verse 37". Research method in this study used literature review research. In this study, researchers found that the concepts of Islamic educational values ??are a collection of life principles, teachings about how humans should carry out their lives in the world, one principle with each other related to forming a unified whole that is inseparable inherent in Islamic education which is used as a basis for humans to achieve the goals of human life that is to be a human being and serve God Almighty. There are two types of Islamic educational values, namely Ilahiyah values ??and Insaniyah values. The results of this study the researchers concluded that the values ??of Islamic education contained in al-Qur'an Surah Ali Imran verse 37: 1). Ilahiyah Values, such as, Faith, Islam, piety, sincerity, trust, gratitude and patience. 2). Insaniyah values ??include al-ukhuwah, tawadhu ', al-wafa, husnudzan., Al-amanah, and al-munfiqun.